System of audiovisual teaching resources for the improvement of regular and irregular verbs pronunciation in the past tense - Pacheco Delgado, Johan Alberto; Ramírez Morales, Génesis Mishel (Machala, 2022)
The purpose of this research is to improve the pronunciation of regular and irregular verbs in the past tense of the English language in students of the Pedagogy of National and Foreign Languages career through the use of ICTs as a didactic resource. Since they provide a wide range of computer materials, which are useful in the new digital educational context. Despite being university students, difficulties persist in terms of pronunciation. The research responds to a qualitative paradigm with an action research design making use of theoretical methods that allowed to organize the different criteria on the subject, facilitating a broader view on the research work. While with the help of empirical methods such as participant observation and diagnostic test which will allow to diagnose the initial state of the study population made up of first semester students of National and Foreign languages Pedagogy (PINE) career of Machala Technical University located in Machala city. Thus, identifying the needs of the students, we resorted to the use of new methodology to correct pronunciation errors within the group of students through the use of tics. The first step is to use virtual classrooms and then working with a set of activities designed to listen to the students and then give way to the practice of the articulation of each verb and thus begin to rectify errors carried over from secondary education.
Esta investigación tiene como propósito perfeccionar la pronunciación de verbos regulares e irregulares en tiempo pasado de la lengua inglesa, en los estudiantes de la carrera de Pedagogía de los Idiomas nacionales y extranjeros mediante el uso de las TICs como recurso didáctico pues las mismas brinda una alta gama de materiales informáticos el cual es útil en el nuevo contexto educativo digital. A pesar de ser estudiantes universitarios siguen persistiendo dificultades en cuanto a la pronunciación. La investigación responde a un paradigma cualitativo, con un diseño de investigación acción, haciendo uso de métodos teóricos que permitieron organizar los distintos criterios sobre la temática, facilitando una vista más amplia sobre el trabajo investigativo, mientras que con ayuda de métodos empíricos como la observación participante y el test de diagnóstico que permitieron diagnosticar el estado de inicial de la población en estudio conformado por los estudiantes de primer semestre de la carrera de Pedagogía de los Idiomas Nacionales y Extranjeros (PINE) de la Universidad Técnica de Machala situada en la ciudad Machala. Es así que identificando las necesidades del alumnado se ha recurrido al uso de nueva metodología para lograr corregir errores de pronunciación dentro del grupo de estudiantes mediante el uso de las TICs. En primer lugar, usando las aulas virtuales para luego trabajar con un conjunto de actividades diseñadas a la escucha de los estudiantes para luego dar paso a la práctica de la articulación de cada verbo y así comenzar a rectificar errores arrastrados desde la educación secundaria.
Keywords: DIDACTIC RESOURCE; TEACHING; LEARNING; ACTIVITY SYSTEM